2015
DOI: 10.1093/infdis/jiv561
|View full text |Cite
|
Sign up to set email alerts
|

Human Polymorphisms in Placentally Expressed Genes and Their Association With Susceptibility to CongenitalTrypanosoma cruziInfection

Abstract: Our results suggest an important role of human polymorphisms in proteins involved in extracellular matrix remodeling and the immune response during congenital infection. To our knowledge, this is the first study demonstrating the association between mutations in placentally expressed genes and susceptibility to congenital infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…8 Recently, it was published that the placental environment upregulates the innate immune response against infection by two stocks of T. cruzi in mice. 48 Here, we present data on some aspects of the innate immune system on the infection of placental chorionic villi explants by two stocks and two inocula of T. cruzi.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recently, it was published that the placental environment upregulates the innate immune response against infection by two stocks of T. cruzi in mice. 48 Here, we present data on some aspects of the innate immune system on the infection of placental chorionic villi explants by two stocks and two inocula of T. cruzi.…”
Section: Discussionmentioning
confidence: 99%
“…Even though distinct strains may display subtle differences in their ability to invade trophoblasts or chorionic villi explants in vitro (Castillo et al, 2013), genetic profiling experiments have conclusively shown that i) the same set of strains circulate in the bloodstream of transmitting and non-transmitting mothers, and ii) nearly identical T. cruzi genetic signatures are recovered from infected infants born to Chagasic mothers coursing concurrent, multi-strain infections (Figure 1) (Burgos et al, 2007; del Puerto et al, 2010; Virreira et al, 2006a). Overall, the actual consensus is that maternal parasite load and human polymorphisms constitute the main risk factors for T. cruzi congenital transmission (Bua et al, 2012; Fabbro et al, 2014; Juiz et al, 2016; Kaplinski et al, 2015; Rendell et al, 2015). …”
Section: Trypanosoma Cruzi An 'All-wheel Drive' Parasitementioning
confidence: 99%
“…Chagas disease (American trypanosomiasis) is caused by the protozoa parasite Trypanosoma cruzi (T. cruzi), which is transmitted to humans by blood-sucking triatomine bugs and by non-vectorial mechanisms, such as contaminated blood transfusion, organ transplantation, and congenital infection [1,2]. Chagas disease is a significant public health burden and the leading cause of death and morbidity in Latin American and Caribbean regions [3].…”
Section: Introductionmentioning
confidence: 99%